EFFECT OF REWARD, PUNISHMENT AND COMMUNICATION ON THE EMPLOYEE PERFORMANCE OF THE FASHION DIVISION AT PT. MITRA ADI PERKASA TBK SURABAYA - Debbynia Nur Rika Sari; Bayu Airlangga Putra; Mochammad Arif (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study aims to determine the effect of simultaneous and partial reward, punishment and communication on the performance of fashion division employees at PT. Mitra Adi Perkasa Tbk Surabaya. This research is quantitative research. Population and sample based on questionnaire distribution to the performance of fashion division employees at PT. Mitra Adi Perkasa Tbk Surabaya was taken as many as 75 respondents. Data collection techniques using interviews, observation and questionnaires. The data analysis used is reliability test, validity test, classic assumption test and multiple linear analysis test. The results of the study simultaneously and partially reward, punishment and communication have a significant effect on the performance of fashion division employees at PT. Mitra Adi Perkasa Tbk Surabaya because of its significance <0.005